(3GdfGaY jhe GdMTQs - (3GdSjhQj, GdMdj, GdCSOj, CHh YHO Gddg, TQa GdOjf, ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826s ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3abGd CHh GdMSjf GdHUQj(B: (3gj YHGQI Yf Ydeg JYGdi HeG aj GdaYd ef GdeUdMI GdOGYjI Edi EjLGOg, hbGd GdfLGQ eYfGg(B: (3Cfg ZjQ eZdhH hdG ecQg aeYfGgG EPf SdHjs
(3BNQgG (B:s
(3BNQgG(B: (3GdQGHY ef GdBeQ hGdfGgj ef GdVQO GdMGUd HSHH GdCeQ hGdfgj eG (B... (3Ch Edi CMO ef GdeSdejf aEf ZdH YfOgeG MUhd Pdc GQJaY GdhLhH CjkVG hjLHGf HGdbdH hGddSGf hGdHOQ dG jfJbd Edi GdCUYH eY GfLGY GdCSgds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 282s
(3GdPQjYI, L (B24: 13s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds